A Review Of The Design Criteria And Practical Aspects Of Developing A Successful Pre-Split. - Simon St J Tose (The Southern African Institute of Mining and Metallurgy, 2006)
The objective of this paper and presentation is to review the different criteria and methodology used by AEL and other organisations to create a pre-split design which delivers a stable highwall for the life of that part of the mining operation. It will look at the need to adapt and change the way, size and direction of the production blasts as the mining phase approaches the highwall position for which a pre-split has been created. Key Words: Pre-split: Design; Highwall; Perimeter